Association between energy cost of walking, muscle activation, and biomechanical parameters in older female fallers and non-fallers - Marques, Nise Ribeiro [UNESP]; Laroche, Dain Patrick; Hallal, Camilla Zamfolini [UNESP]; Crozara, Luciano Fernandes [UNESP]; Morcelli, Mary Hellen [UNESP]; Karuka, Aline Harumi [UNESP]; Navega, Marcelo Tavella [UNESP]; Gonçalves, Mauro [UNESP] (Elsevier, 2013)
Objective: To determine the nervous activation, muscle strength, and biomechanical parameters that influence the cost of walking in older fallers and non-fallers. Methods: Maximal voluntary isokinetic torque was measured for the hip, knee and ankle of older women. Oxygen consumption was measured at rest and during 8 min of walking at self-selected speed. An additional minute of walking was performed to collect kinematic variables and the electromyographic signal of trunk, hip, knee, and ankle muscles, which was analyzed by the linear envelope. Cost of walking was calculated by subtracting resting body mass-normalized oxygen consumption from walking body mass-normalized oxygen consumption. Stride time and length, and ankle and hip range of motion were calculated from kinematic data. Findings: Older adult fallers had 28% lower knee extensor strength (p = 0.02), 47% lower internal oblique activation at heel contact (p = 0.03), and higher coactivation between tibialis anterior and gastrocnemius lateralis in each of the gait phases (p < 0.05). For fallers, a higher activation of gluteus maximus was associated with a higher cost of walking (r = 0.55, p < 0.05 and r = 0.71, p < 0.01, before and after heel contact, respectively). For non-fallers, an association between cost of walking and age (r = 0.60, p = 0.01) and cost of walking and thigh muscle coactivation (r = 0.53, p = 0.01) existed. Interpretation: This study demonstrated that there may be links between lower-extremity muscle weakness, muscle activation patterns, altered gait, and increased cost of walking in older fallers. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Aging; EMG; Fall risk; Gait; Kinematic; Biomechanical parameters; Electromyographic signal; Kinematic variables; Muscle coactivation; Oxygen consumption; Aging of materials; Biomechanics; Kinematics; Muscle; Physiological models; Costs; aged; ankle; biomechanics; body mass; bone strength; clinical article; controlled study; electromyography; energy cost; falling; female; gait; gastrocnemius muscle; gluteus maximus muscle; heel; hip; human; kinematics; knee; muscle strength; oxygen consumption; priority journal; range of motion; rest; thigh; tibialis anterior muscle; torque; trunk; velocity; walking